TEACHER’S QUESTIONS IN ENGLISH CLASSROOMS AT SENIOR HIGH SCHOOLS - Andriyadi Andriyadi; Dedi Sofyan (JOALL (Journal of Applied Linguistics and Literature), 2018)
The aim of this research was to investigate teacher’s questions based on the levels and functions of questions in English classrooms at Senior High Schools. The study was a descriptive qualitative. The subjects of this research were six EnglishSenior High School teachers In Rejang Lebong Regency. For collecting the datatape recording, observation checklist and interview were employed. Result related toresearch questions showed that the teacher’s questions were categorized remembering, comprehending and applying and analyzing level. None of the teachers used questions in, evaluating and creating level of the Bloom’s Taxonomy.In the research only five function of questions were found namely: practicing skills,checking prior knowledge, recapping, and checking understanding. From thefinding it can be concluded that The questions asked by the teachers in classroomsare in lower order cognitive level and not all function of questions (from elevenfunction of questions) were applied by the teachers.